Meningkatkan Kemampuan Berpikir Kritis Pada Perkuliahan Geometri Bilangan Kompleks Dengan Discovery Learning Dipadukan Dengan Cooperative Learning Tipe NHT (Numbered Head Together) - Turmuzi, Muhammad; Sarjana, Ketut; Junaidi, Junaidi (Mandalika Mathematics and Educations Journal, 2021)
The purpose of this study is to improve students' critical thinking skills in Geometry lectures through discovery learning combined with NHT Type Cooperative Learning. This research uses a class action research approach. Each cycle consists of several stages, namely: planning, action, observation, and reflection. At the planning stage consists of learning plan preparation activities, the preparation of research instruments, at the action stage includes the activities of providing action in the form of learning in accordance with the learning design that has been formed in accordance with the principles of discovery learning combined with NHT Cooperative Learning Type, the observation stage includes observation activities on student activities during learning, especially during discussions and the implementation of actions and obstacles encountered, and the reflection stage is a reflection of the implementation of learning activities based on observations and results of critical thinking skills through insertion tests. Matters of concern at this stage of reflection are the assessment of the implementation of actions, the obstacles that arise, and the progress that has been achieved. To obtain research data two types of research instruments were used. The research instrument in question is the observation sheet of the implementation of learning and observation guidelines as well as test questions on critical thinking skills at the end of the cycle. The results of this study indicate that the average percentage of students' critical thinking skills increased from cycle I to cycle II, namely 62.25% in cycle I increased to 81.70% in cycle II.